Bello's Leadership Style: A Lesson for the Nigeria's Political Leadership - Muhammad Dahiru Shuni (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
Objective: This research explores the leadership values of Sultan Muhammad Bello and their relevance to contemporary Nigerian political and administrative systems. Sultan Muhammad Bello, the son of Shaykh Uthman B. Foduye, played a key role in establishing the Sokoto Caliphate in West Africa. Educated under his father’s guidance and by prominent scholars, Bello's leadership qualities shone in jihad warfare and governance. The study aims to examine how Bello's principles can address modern challenges in Nigeria's democratic governance, including corruption, political fragmentation, and social injustice. Theoretical framework: Theoretical underpinnings are rooted in Islamic leadership principles, emphasizing justice, consultation (shura), knowledge, and service to the public. These values are juxtaposed with the demands of contemporary governance, highlighting their timeless relevance. Literature Review: The literature review provides a comprehensive examination of Bello’s written works and historical records, shedding light on his leadership philosophy and its alignment with Islamic values. Methods: This qualitative research employs a descriptive-analytical method, with data gathered from primary sources, such as Bello’s writings, and secondary sources, including historical and scholarly analyses. The data is organized into thematic sub-topics: Nigerian politics and administration, leadership selection, candidate qualifications, obedience to authority, unity, public service, security, justice, economic empowerment, and consultation. Results: The findings reveal that Bello's leadership principles remain highly pertinent. His emphasis on justice, public service, consultation, and unity provides a robust framework for addressing governance challenges in Nigeria. Moreover, his focus on education and economic empowerment underscores the importance of knowledge and capacity building in fostering societal progress. Bello’s values promote inclusivity and effectiveness in governance, offering solutions to the complexities of Nigeria’s diverse and modern democratic system. Implications: The study's implications highlight the potential of Bello's leadership principles in fostering transparent governance and reducing corruption. The emphasis on unity and justice can mitigate political fragmentation and social inequality, while his advocacy for knowledge and economic empowerment aligns with sustainable development goals. Novelty: The novelty of this research lies in its contextual approach, bridging traditional Islamic leadership values with contemporary Nigerian political needs. It contributes significantly to the discourse on Islamic leadership in West Africa, providing insights for policymakers and academics interested in reconstructing leadership paradigms for effective nation-building.